EFFECTIVENESS OF VERMICOMPOST IN SUBSTITUTING UREA FOR PROMOTING GROWTH AND YIELDS OF MUNG BEAN (Vigna radiata L.) IN ULTISOLS - Evendi Tri Mulyono; Hesti Pujiwati; Fahrurrozi Fahrurrozi; Bambang Gonggo Murcitro; Supanjani Supanjani; Hasanudin Hasanudin (BPFP Universitas Bengkulu, 2023)
Vermicompost is one of increasingly applied organic fertilizer to many vegetable crops in order to reduce the dependency on synthetic fertilizer, including the use of urea as nitrogen source. This experiment aimed to determine the best dosage combination of vermicompost and synthetic urea on growth and yields of mung bean grown in Ultisols. This experiment was arranged in a randomized complete block design with three replicates. Treatments consisted of (1) control, no urea and no vermicompost, (2) 50 kg/ha urea + no vermicompost, (3) 40 kg/ha urea + 3 Mg/ha vermicompost, (4) 30 kg/ha urea + 6 Mg/ha vermicompost, (5) 20 kg/ha urea + 9 Mg/ha vermicompost, (6) 10 kg/ha urea + 12 Mg/ha vermicompost, and (7) 0 kg/ha urea + 15 Mg/ha vermicompost. Results indicated that the combination of urea and vermicompost increased plant height, leaf number, branch number, number of nodules/plant, shoot to root ratio, number of pods/plant, number of pods/plot, grain dry weight/plant, grain dry weight/plot, and total yield /ha, but not days to flowering and weight of 100 grains. The best combination to increased growth and yields of mung bean was 12 Mg/ha of vermicompost in combination with 10 kg/ha of urea. This combination produced the highest grain yields/ha (2.1 Mg/ha).